2000
DOI: 10.1002/1099-1468(200003)21:2<63::aid-mde964>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of National Football League teams

Abstract: Most recent empirical analyses of production in the sports economic literature have focused on Major League Baseball. This paper extends that literature by analysing football production in the National Football League (NFL). Using the Poisson regression model, we measure the performance of NFL teams and head coaches. The measure is based on a production process where player skills are converted into games won. The evidence reveals that quality coaching is an important component in the production process. It ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 13 publications
0
54
1
4
Order By: Relevance
“…This approach fails to account for the complex and dynamic nature of soccer in which physical and technical indicators interact (McGarry & Franks, 2003;Reed & O'Donoghue, 2005), thus more studies are needed that utilise such a mixed approach. The most popular technical indicator in soccer is ball possession due to its strong association with success (Bate, 1988;Carmichael, Thomas, & Ward, 2001;Dawson, Dobson, & Gerrard, 2000;Garganta, 2000;Gomez & Alvaro, 2002;Hadley, Poitras, Ruggiero, & Knowles, 2000;Hughes & Bartlett, 2002;James, Jones, & Mellalieu, 2004;Lago & Dellal, 2010;Lago & Martin, 2007;McGarry & Franks, 2003) but this relationship is highly complex with the efficiency of passing (e.g. higher passes to shots on goal ratio) and the type of offensive strategy (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach fails to account for the complex and dynamic nature of soccer in which physical and technical indicators interact (McGarry & Franks, 2003;Reed & O'Donoghue, 2005), thus more studies are needed that utilise such a mixed approach. The most popular technical indicator in soccer is ball possession due to its strong association with success (Bate, 1988;Carmichael, Thomas, & Ward, 2001;Dawson, Dobson, & Gerrard, 2000;Garganta, 2000;Gomez & Alvaro, 2002;Hadley, Poitras, Ruggiero, & Knowles, 2000;Hughes & Bartlett, 2002;James, Jones, & Mellalieu, 2004;Lago & Dellal, 2010;Lago & Martin, 2007;McGarry & Franks, 2003) but this relationship is highly complex with the efficiency of passing (e.g. higher passes to shots on goal ratio) and the type of offensive strategy (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong association between ball possession and success (Bate, 1988;Carmichael et al, 2001;Dawson et al, 2000;Garganta, 2000;Gomez & Alvaro, 2002;Hadley et al, 2000;Hughes & Bartlett, 2002;James et al, 2004;Lago & Martin, 2007;McGarry & Franks, 2003), we expected HPBPT to be technically superior to LPBPT. Our data supports this notion as players in HPBPT performed 44% more passes than those in LPBPT and this trend was also evident for successful passes, received passes, touches per possession, shots, dribbles, tackled events, and final-third entries.…”
mentioning
confidence: 99%
“…In particular, a substantial literature examined the MRP of a player in terms of "the ability or performance that he contributes to the team" (Scott, Long, & Somppi, 1985, p.52), and tested whether players' salaries reflect their levels of MRPs (e.g., Krautmann, 1999;Scott et al, 1985;Scully, 1974). In addition, while less attention has been paid to the direct relationship between MRP and compensation of coaches, several researchers have shown that coaches can have a great effect on the performance of their teams, implying their high MRP in relation to team success (Frick & Simmons, 2008;Hadley, Poitras, Ruggiero & Knowles, 2000;Kahn, 1993). Kahn (1993), for example, demonstrated that the managerial quality of Major League Baseball (MLB) managers predicted by their past performance and experience significantly explained winning percentages of their teams, after controlling for the levels of player input.…”
Section: Positive Relationship Between Past Performance and Total Commentioning
confidence: 91%
“…Kahn (1993), for example, demonstrated that the managerial quality of Major League Baseball (MLB) managers predicted by their past performance and experience significantly explained winning percentages of their teams, after controlling for the levels of player input. Hadley et al (2000) also estimated that highly efficient National Football League (NFL) coaches could allow their teams to gain an additional three to four wins in a season. Similarly, Frick and Simmons (2008) examined the performance data of coaches in the Bundesliga (Germany's premier soccer league) over a 22 year period, finding that head coaches with better quality had the ability to improve the performance of their teams.…”
Section: Positive Relationship Between Past Performance and Total Commentioning
confidence: 99%
See 1 more Smart Citation